2021
DOI: 10.1016/j.jamda.2020.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Social Connection in Long-Term Care Homes: A Scoping Review of Published Research on the Mental Health Impacts and Potential Strategies During COVID-19

Abstract: Objectives: Good social connection is associated with better health and wellbeing. However, social connection has distinct considerations for people living in long-term care (LTC) homes. The objective of this scoping review was to summarize research literature linking social connection to mental health outcomes, specifically among LTC residents, as well as research to identify strategies to help build and maintain social connection in this population during COVID-19. Design: Scoping review. Settings and Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 176 publications
3
135
0
2
Order By: Relevance
“…Several studies highlighted high levels of dissatisfaction and anxiety among nursing home personnel, including financial, psychological, and work-related stressors [ 6 , 55 ]. Many nursing home employees worked multiple jobs and, in some reports, up to 20% were worrying about their own food supplies [ 27 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies highlighted high levels of dissatisfaction and anxiety among nursing home personnel, including financial, psychological, and work-related stressors [ 6 , 55 ]. Many nursing home employees worked multiple jobs and, in some reports, up to 20% were worrying about their own food supplies [ 27 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of COVID-19 deaths that occurred in nursing homes is high. In May 2020, it was estimated that about half of the COVID-19 deaths in France and Ireland were from nursing homes, with even higher proportions reported in the US and Canada [ 5 , 6 ], and high numbers of excess deaths in nursing homes reported in England and Wales [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research studies conducted in LTC homes have demonstrated that social connection is linked to mental health outcomes including depression, cognitive decline, and behavioural symptoms of dementia. ( 8 ) Similarly, studies have also shown social connection is associated with physical health outcomes for LTC residents, including mortality ( 9 ) and self-rated health. ( 10 ) For residents of LTC homes, family and friends provide crucial social support, from hands-on assistance (e.g., during meals) to ensuring that staff understand who a resident is as a person and within a unique life history.…”
Section: Social Connection Supports the Mental And Physical Health Of Ltc Residentsmentioning
confidence: 98%
“…( 3 ) However, qualitative studies with older adults have found that maintaining contact with others (in person or by phone or other means) and engaging in (even solitary) purposeful activity are key strategies to prevent loneliness. ( 3 ) A recent scoping review of published observational and intervention research conducted in LTC homes that assessed social connection outcomes ( 8 ) highlighted 12 low-cost strategies that could be adapted for COVID-19 or other disease outbreaks. These strategies can be implemented right now to help build and maintain social connections with LTC residents:…”
Section: Strategies That Can Help Build and Maintain Social Connection For Ltc Residentsmentioning
confidence: 99%
“…Residents' cognitive impairment may also be a factor in their low level of social engagement and inability to enter into meaningful relationships with others. Good social connection has been associated with good mental health outcomes in LTC residents (Bethell et al, 2021). Meaningful social engagements are essential as they are associated with quality of life in LTC facility residents (Kehyayan et al, 2015;Morris et al, 2018).…”
Section: Discussionmentioning
confidence: 99%